Circadian-based processes in the High Arctic: activity, thermoregulation and photoperiodism in the Svalbard ptarmigan (Lagopus muta hyperborea) - Appenroth, Daniel (UiT The Arctic University of Norway, 2021)
This thesis addresses aspects of the circadian and photoperiodic system in a High Arctic bird: the Svalbard ptarmigan ( Lagopus muta hyperborea , Sundevall 1845). The most northern resident bird inhabits a unique photic environment; 2/3 of its year it spends either under a night without sunrise (polar night) or under a never setting Sun (polar day). Studies so far suggest a temporal loss of circadian control over behaviour during these constant photic conditions, allowing opportunistic rather than circadian dictated behaviour. Yet, circadian control extends beyond temporal organisation of behaviour, and other aspects of this Arctic-adapted circadian machinery have received less attention. Rhythms in core body temperature (T b ) have not been thoroughly studied in Svalbard ptarmigan and in Arctic birds in general and the extent of circadian control over this physiological parameter is unknown. In paper I, we have investigated the T b rhythm alongside activity in captive Svalbard ptarmigan under short photoperiod (SP), long photoperiod (LP) as well as under constant light (LL) and constant darkness (DD). While birds under SP and LP showed clear diurnal activity and T b patterns, these rhythms seemed to be lost under LL and DD. However, under SP we noticed nocturnal rise in T b in anticipation to the light-on signal, a rise which also preceded rise in activity. Anticipation is a hallmark of circadian rhythmicity and indicates circadian control of thermoregulation in Svalbard ptarmigan. In an additional experiment (unpublished), we transferred Svalbard ptarmigan entrained to L:D 12:12 into either LL or DD and measured dampening in T b cycles by sine wave and periodogram analysis. The results show that T b cycles dampened under DD and LL before becoming arrhythmic. It is further shown that the T b rhythm dampened faster under LL (rhythm dampened by half after 1d 23h in LL) than under DD (rhythm dampened by half after 5d 12h). While T b and activity might be useful parameters to characterise circadian organisation, ...